The Joy of Pain-Things : Strategies Used in Translating Wordplay and Onomatopoeia in Belzebubs - Nikula, Riikka (My University, 2021)
This study aimed to examine the strategies used in translating wordplay and onomatopoeic effects in the Finnish, French, and Swedish translations of JP Ahonen’s comic book Belzebubs, which was originally written in English. The object was to determine if there are significant differences between the translations, which strategies were most frequently used, and whether the translations are more domesticating or foreignizing in nature. The research material consisted of 46 cases of wordplay and 122 instances of onomatopoeia found in the source text. The wordplay was categorized, and the translations of each language were analyzed in order to assess which translation strategies had been used. The most popular types of wordplay in the original book were wordplay based on morphology and using allusions. The favored translation strategy across all languages and wordplay categories was turning source language wordplay into target language wordplay whenever possible. Overall, the use of different strategies was quite similar in all translations. The research showed that roughly half of the onomatopoeia in dialogue had been translated, as opposed to the small percentage of translated effects outside of dialogue. The ones left untranslated were predominately ones embedded in the graphics, or ones that are universally understood. The translations were not clearly either domesticating or foreignizing. The results indicate that translating wordplay is possible, and that dynamic equivalence can be achieved in the translations, although diverse strategies must be utilized in order to produce the best possible translation.
Keywords: translation, wordplay, onomatopoeia, translation strategy, comics